Acceptability of a COVID-19 Vaccine Among Healthcare Workers in the Kingdom of Saudi Arabia - Qattan, Ameerah M. N.; Alshareef, Noor; Alsharqi, Omar; Al Rahahleh, Naseem; Chirwa, Gowokani Chijere; Al-Hanawi, Mohammed Khaled (Frontiers in Medicine, 2021)
Objective: This study aims to determine the acceptability of a COVID-19 vaccine among healthcare workers in Saudi Arabia and the factors affecting their intention to accept the vaccine. Methods: The study used data from an online cross-sectional survey that was conducted in Saudi Arabia between 8 December 2020 and 14 December 2020. This study employed bivariate and multivariable regression analyses. The bivariate was used to describe and tabulate the frequency of all the variables, including the sociodemographic characteristics, the risk perception and the acceptance of the COVID-19 vaccination and a chi-squared test of independence was calculated. Multivariable logistic regression models were employed to examine and identify the factors associated with an intention to have the COVID-19 vaccination and the factors associated with its immediate acceptance. Results: Of the total of 736 healthcare workers who began the online questionnaire, 673 completed it (a 91.44% completion rate). Among the study participants, 50.52% were willing to have the COVID-19 vaccine, of which 49.71% intended to have the vaccine as soon as it becomes available in the country, while 50.29% would delay until the vaccine’s safety is confirmed. Being a male healthcare worker, perceiving a high risk of infection and believing that the COVID-19 vaccine should be compulsory for all citizens and residents in the country increased the probability of intention to vaccinate against COVID-19 and the probability of accepting the COVID-19 vaccination as soon as possible. Conclusion: This study calls for more health-related education among healthcare workers to alleviate any fears that might be associated with the COVID-19 vaccine.